ANALISIS PENGGUNAAN BAHASA SMS UCAPAN SELAMAT IDUL FITRI 2011 - Adhani, Agnes (Widya Warta, 2013)
ABSTRACTThe study discusses Short Message Services (SMSâ€™s) used to express â€œHappy Idul Fitriâ€ in relation to politeness principle and cooperative principle.The aims of the research are (1) to describe the way of writing the SMSâ€™s, (2) to explain the sentence variety of the SMSâ€™s, (3) to describe the language used in the SMSâ€™s, (4) to explain the variety of relation between the writers and the reader of the SMSâ€™s, and (5) to describe communicative act found in the SMSâ€™s.This research is descriptive-qualitative in nature. The data are 54 SMSâ€™s used to express â€œHappy Idul Fitriâ€ in 2011. The SMSâ€™s were received by the reseacher from her friends and colleagues. All of the SMSâ€™s were analyzed to reveal the five aims of the research as stated above.The expressions of â€œHappy Idul Fitriâ€ are found in the initial, middle, and final parts of the SMSâ€™s. Some of them made use of associative language.Due to their variety, the sentences applied in the SMSâ€™s expressing â€œHappy Idul Fitriâ€ are (1) declarative, (2) imperative, and (3) exclamatory.The languages used in the SMSâ€™s include (1) Indonesian, (2) Indonesian-Arabic, (3) Indonesian-Javanese, (4) Javanese, (5) Indonesian-English, and (6) Indonesian-Arabic-English.While, the relations between the writers and the reader of the SMSâ€™s are of five kinds, namely (1) intimate parallel, (2) respectful parallel, (3) lower respectful writers, (4) lower intimate writers, and (5) neutral parallel.The variety of communicative act used in the SMSâ€™s comprises (1) to express â€œHappy Idul Fitriâ€, (2)to apologize, (3) to expect, and (4) to thank.